Current Controversies on the Control of Religious Organizations in Japan - Okudaira, Yasuhiro (Columbia Journal of Asian Law, 1996)
During the early days of 1995, it looked as if Japan was under some curse. On January 7, the Kobe area was struck by an earthquake of great magnitude, killing more than 5,500 people and injuring thousands more as well as causing property damage on an enormous scale. And on March 20, highly poisonous sarin gas was released in various places throughout the Tokyo subway system, depriving 12 people of their lives and causing injuries to hundreds more. Ten days after the subway incident, on March 30, Koji Kunimatsu, Inspector General of the National Police Bureau, was the victim of an unknown, would-be assassin. All of these unusual events took place in rapid succession within a very short time. In light of the widely held belief that the Tokyo metropolis, despite its dense population and high level of industrial activity, was one of the safest cities in the world, the sarin incident in the Tokyo subway system greatly shocked people throughout the world. It became all too clear that any populous place in the world could be a target of attack by fierce and indiscriminate terrorists.